Determinants of Millennial Farmers’ Decisions in Hydroponic Melon Cultivation: Evidence from Sragen Regency - Prasetyo, Agung; Budiyono, Agus; Wulandari, Ria Agustina; Aji, Diyan (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
One of the fruits that is in demand by consumers with a fairly high economic value is melon. Melon plants are native to Africa that have many vitamins and minerals that are useful for body health. Millennial farmers have recently been involved in the hydroponic melon business because it has a high selling value. This study aims to determine the factors that influence the hydroponic cultivation decisions of millennial farmers. The study was conducted in several sub-districts in Sragen Regency, including Gemolong, Plupuh and Masaran. The sampling method was carried out using the Snowball sampling method. This study utilized various data analyzes used for SEM-PLS analysis. This study examined factors influencing farmers’ decisions to cultivate hydroponic melons, focusing on technical, economic, social, and cultural aspects. Respondents were mostly young men with limited experience but high learning potential. Production outcomes varied widely, reflecting diverse capacities. Validity and reliability tests confirmed robust measurement. Effect size and path analysis revealed that decisions were dominantly shaped by technical (f² = 0.819, negative effect) and economic (f² = 0.391, positive effect) factors, while social and cultural aspects were minor. The study highlights technology complexity and economic constraints as key barriers, suggesting training, accessible facilities, and market support as priority strategies.